Spectrum of Flat Epithelial Atypia in Breast Lesions - Nazish Jaffar; Amna Khan; Rabisa Batool; Noshaba Rahat (Life and Science)
Objective:  To determine the frequency of flat epithelial atypia and its association with  breast lesions in trucut biopsies and lumpectomy specimens in the local population. Study Design: A cross-sectional study. Place and Duration of Study: The study was conducted in the Department of Pathology at Basic Medical Sciences Institute, Jinnah Postgraduate Medical Center Karachi, Pakistan, from October 2019 to September 2022. Methods: In total, 286 biopsy specimens of breast tissue diagnosed with various pathologies, including benign and malignant cases, were included in our study. The overall frequency of flat epithelial atypia was noted. Furthermore, the Fischer Exact/Chi-square test of association was applied to observe the association of FEA with other breast lesions. Open Epi software was utilized for sample size calculations, and data was analyzed with SPSS version 22.0. Results: The most common age range for flat epithelial atypia  was 17 to 80 years, and the mean age was 27.05 ± 10.34 SD. Fibroadenoma was the most frequent clinical presentation in 214 (74.8%) cases. Features of  flat epithelial atypia were found in a total of 11 (3.84%) cases. However, Ductal Carcinoma in Situ (DCIS) showed 100% positivity for flat epithelial atypia followed by fibrocystic disease (62%), Invasive Ductal Carcinoma( IDC) (15%), and adenosis (12.5%). Conclusion:  The frequency of flat epithelial atypia, was 3.84% in trucut biopsies and lumpectomy specimens of the breast. The Ductal Carcinoma in Situ (DCIS), IDC, fibrocystic disease, and adenosis showed a positive association with flat epithelial atypia.